Atributos físicos e químicos do solo e desempenho agronômico da cultura da soja submetido a sistemas de manejos e residual de gesso - Freitas, Leandro Alves [UNESP] (2015)
The land use for agricultural production in the cerrado was established, with intensive tillage systems. However, with the intensification of preparation, physical and chemical soil properties were changed as management applied. In order to know and understand the influence of some handling sequences of combined soil with the use of gypsum. We carried out this work during the growing 2011 to 2013 in succession of the corn and soybean crops in the winter in the summer at the Experimental Farm Research & Extension UNESP, Ilha Solteira - SP. The soil was classified Hapludox, clayey (EMBRAPA, 2013). The experimental design was a randomized block design, combining four cultivation systems: direct sowing Continuous (SPD-SPD) and Alternate (SPD-CM), Minimum Cultivation Continuo (CM-CM) and Alternate (CM-SPD) with or without the use of plaster, and four replications. The physical characteristics were evaluated macroporisidade (Ma) and micro (Mi), total porosity (Pt) and bulk density (Ds) and chemical (P; MO; PH; k; Ca, Mg, H + Al, Al, V (%) of the soil and the agronomic characteristics of the soybean crop. The results dismounted no-tillage system still got the best physical, chemical soil and agronomic soybean, due to its better maintenance of stable aggregates and pores over time in profile, still allowing an increase in total porosity (Pt) and decreased soil bulk density (Ds) with the use of gypsum. Also, with few variations in chemical properties, obtaining more stable values in the two seasons and depths, with the highest values for organic matter (MO), potassium (K), calcium (Ca), magnesium (Mg), and one of the values lower for aluminum (Al). The gypsum provided better nutrient availability in the soil profile regardless of the employee soil management. Also in the till and this gave the highest values for the initial population, end, grains and productivity in two soybean crops, but did not get the highest